ASAS PEMBUKTIAN TERBALIK DALAM TINDAK PIDANA KORUPSI (PERSPEKTIF HUKUM PIDANA INDONESIA DAN HUKUM PIDANA ISLAM) - Gazali Rahman; La Jamaa (TAHKIM, 2022)
This study examines the main problems; “How the principle of reversed of proof in corruption perspective Indonesian criminal law and Islamic criminal law?” The problem was studied by juridical, and shariah approach, and analyzed by qualitative descriptive. Data were collected through library research. The results showed: the principle of reversed of proof in corruption perspective Indonesian criminal law, has implied in Law No. 3 of 1971, and Law No. 31 of 1999 jo. Law No. 20 of 2001. However, the Corruption Court in Indonesia have yet to implement the principle of reversed of proof in corruption to the fullest. Islamic criminal law also adheres to the principle of reversed of proof in corruption. It can be explored from dalalah 'ibarah Koran Surah Al-Nisa verse 135, also the story of Prophet Yusuf evidence on charges Zulaikha in Koran Surah Yusuf verse 24-29, and asbab al-nuzul Koran Surah Ali Imran verse 161, and the Prophetic traditions, and rules of fiqh. The principle of reversed of proof in corruption perspective Indonesian criminal law is limited and balanced. While the principle of reversed of proof in corruption perspective of Islamic criminal law is absolute.Keywords: principle reversed of proof, corruption, indonesian criminal law, islamic criminal law